Factors Associated With Prostate Cancer Screening Adherence Among Retired Men in Togo, 2023 - Diguibe Tien-Bale Bamide; Latame Komla Adoli; Sêdégnon Benoît Agossoukpe; Roméo Mèdéssè Togan; Hermine Tognon; Ismaël Simpore; Dieudonné Soubeiga (American Journal of Men's Health)
Prostate cancer is the leading male cancer in sub-Saharan Africa, with 74,878 (17.4%) new cases and 32,390 (11.6%) deaths in 2022. In Togo, the total number of prostate cancers was 726 in 2021. Screening methods are readily available in Togo. However, prostate cancer is still detected at a late stage. This study aimed to determine the factors associated with adherence to prostate cancer screening among retired men in Togo, 2023, using the Health Belief Model. A national descriptive and analytical exploratory cross-sectional study was carried out from March 1 to May 31, 2023. A total of 288 retirees were included. Overall, 54.9% of retirees perceived their vulnerability to prostate cancer, 54.9% perceived its severity, 52.4% perceived barriers to screening, 50.3% perceived benefits from screening, 53.1% perceived their self-efficacy for screening, and 55.2% perceived cues to action. A total of 83% of retirees agreed to undergo prostate cancer screening. The absence of a history of chronic pathology (adjust odds ratio [aOR] = 3.0, 95% CI [1.4, 6.2], p  = .010), frequency of annual medical consultation (aOR = 0.3, 95% CI [0.1, 0.8], p  = .020), perceived obstacles (aOR = 0.4, 95% CI [0.2, 0.9], p  = .029) and perceived cues to action (aOR = 5.1, 95% CI [1.9, 15.1], p  = .002) are significantly associated with adherence to prostate cancer screening. This study reported a high level of adherence to prostate cancer screening among retirees. It demonstrated that the absence of a history of chronic pathology, frequency of annual medical consultation, perceived barriers, and perceived incentive to action were significantly associated with adherence to prostate cancer screening.